POSTHARVEST EDIBLE COATING TREATMENTS OF JOJOBA AND HIBISCUS OIL TO IMPROVING QUALITY AND STORABILITY OF HASS AVOCADO FRUITS DURING COLD STORAGE - Eman Abd El-Moniem; Amr Abdelkhalek; Aml Yousef; Ahmed Badr; Adel Abdel-Razek (Mesopotamia Journal of Agriculture)
The edible coatings and films extend the postharvest life of fresh fruits. It is used to improve the' appearance of fruits and ensure their safety due to its environmentally friendly nature. The present study was conducted during the 2021 and 2022 seasons to investigate the effect of some edible coatings, such as oils of jojoba (Simmondsia Chinensis), Hibiscus (Hibiscus sabdariffa), or their mixture (1:1), on the quality and storability of avocado fruits cv. Hass. The fruits were stored under cold storage conditions (5 ± 1°C/ and 85 - 90% RH/ 6 weeks) compared with untreated fruits (control). The initial contamination of toxigenic fungi was determined for the collected avocado fruits. Also, the ability of treated fruits to resist fungal contamination was evaluated using a simulated experimental study. The results showed that all edible coating treatments cleared better physical and chemical properties during storage than untreated fruits (control). Avocado fruits coated with hibiscus extract resulted in the highest fruit firmness, vitamin C content, chlorophyll content, the least titratable acidity, and negligible phenol content. The Jojoba treatment showed the highest soluble solid content and chlorophyll b content. Generally, edible coatings with jojoba oil and hibiscus extract and their mix (1:1) can be recommended to preserve the fruit quality and extend avocado fruits' storage life.